Demonstration of the shorter flagellin (flaA) gene of urease-positive thermophilic Campylobacter isolated from the natural environment in Northern Ireland - Gondo, T; Sekizuka, T; Manaka, N; Murayama, O; Millar, B C; Moore, J E; Matsuda, M (Folia microbiologica, 2006)
The PCR amplicons (about 1450 bp in length) of flaA gene fragments of 11 isolates of urease-positive thermophilic Campylobacter (UPTC) isolated from the natural environment not including wild birds in Northern Ireland were demonstrated to be shorter than those of C. jejuni 81116 and six isolates of C. jejuni and C. coli (about 1700 bp) isolated in Northern Ireland and Japan. When the nucleotide lengths of the possible open reading frame (ORF) of the flaA genes were determined, those from the 11 UPTC isolates were estimated to be 1464-1503 bp, and those from the six C. jejuni and C. coli isolates and C. jejuni 81116 strain to be 1716-1728 bp. Nucleotide sequence and deduced amino acid sequence alignments of the possible ORFs demonstrated that the ORFs from the 11 UPTC isolates lack about 80 amino acid residues, mainly from the approximate residue numbers 390-470 of the large variable region in the flaA protein of the seven isolates of C. jejuni and C. coli, and do not have any internal termination codons. High amino acid sequence similarity of both amino- and carboxy-termini of the ORFs of the flaA gene was demonstrated between the 11 isolates of UPTC and the 7 isolates of C. jejuni and C. coli. The 11 UPTC isolates examined were strongly suggested to possess a shorter flaA gene without any internal termination codons.
Keywords: Molecular Sequence Data; sekvence aminokyselin; Campylobacter coli; Urease; Sequence Alignment; Open Reading Frames; flagelin; polymerázová řetězová reakce; Polymerase Chain Reaction; Flagellin; ureasa; Japonsko; Northern Ireland; Amino Acid Sequence; Campylobacter jejuni; otevřené čtecí rámce; Severní Irsko; Japan; molekulární sekvence - údaje; Sequence Analysis, Protein; sekvenční analýza proteinů; sekvenční seřazení